Evaluation of the Detrimental Effects of some Antiepileptic Drugs on the Height and Weight of Children with Epilepsy - Ahmed AlKataan, Muhammad Abdulgafoor; Abdullah Shakir Mahmood; Aseel S. Al Mallakhdeer (Iraqi Journal of Pharmaceutical Sciences, 2022)
Growth is a multifactorial process influenced by genetic, nutritional, hormonal, psychosocial and other factors including the general health of a child. Epilepsy defined as a chronic condition characterized by recurrent clinical events or epileptic seizures, which occur in the absence of a metabolic or toxic disease the drugs that use in the treatment of this condition can affect patients growth due to their mechanisms of action. This study aimed to evaluate the effect of some antiepileptic drugs on growth (height and weight) in children with epilepsy. This work involved 51 newly diagnosed children with a different form of epilepsy (Generalized, absent and partial). Patients divided into three groups according to the treatment (group one patients on Carbamazepine monotherapy with dose mean 13.3 ± 4.8 mg/Kg, group two patients on Valproic acid monotherapy with a dose of 14.4± 3.3 mg/kg and the last group involve patient on combined therapy Carbamazepine 10.8±5.8 plus 19.7± 8.8 of Valproic acid. Patients age range from 5-11 years, with an Initial BMI range of 12-20. The results of this work showed that Carbamazepine monotherapy caused no significant affected on both BMI values after 6 and 12 months of treatment (p>0.05). Valproic acid monotherapy significantly elevated BMI after 6 and 12 months of treatment (p>0.01). Combined therapy showed no significate effect on BMI. The patient’s centile height significantly elevated after 6 and 12 months of Valproic acid (p<0.01) compared to the normal growth according to the growth chart. While both Carbamazepine and combined therapy showed no significant change in comparison to the normal growth according to the growth chart (p>0.05). In conclusion, children with epilepsy who use antiepileptic drugs need restricted monitor policy for their growth, especially those on Valproic acid.